PENDAMPINGAN MANAJEMEN USAHA DAN PENINGKATAN KUALITAS PRODUK UMKM KOPI ADAT SEGUNUNG CARANGWULUNG JOMBANG - Riyadi Nugroho; Gustaf Naufan Febrianto (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The purpose of IBM activities for this community is to provide business management assistance and appropriate technology for Small Businesses engaged in coffee powder in Carangwulung Village Customary Hamlet, Wonosalam Subdistrict, Jombang Regency.  The target of this PKM activity is the owner and business manager in the field of coffee called Kopi Adat. The problem faced by This Customary Coffee SME is the low ability to manage the business without any planning, organizing, bookkeeping, and evaluation. In addition, there is also no proper marketing strategy only selling around the location; besides, the coffee milling process is still done in the rental place, so mix with other people's coffee because it does not have its mill. Looking at the situation above, we have done transfer of knowledge and mentoring to carry out management functions, provide coffee milling technology, develop and execute marketing strategies so that products can sell well so that there is business sustainability by providing understanding and mentoring to manage the business well, improve product quality with TTG and be able to market products so that they can achieve benefits in improving well-being. Existing owners and labor and there are a sustainable in their business. The initiator of the activity and partners have carried out activities, namely the handover of coffee milling machines, training and mentoring of business management and financial bookkeeping, and marketing products to sell in the market